Effect of matrix metalloproteinases on the healing of diabetic foot ulcer: A systematic review. Issue 1 (February 2023) - Zhang, Wan-Qing; Tang, Wen; Hu, Shi-Qi; Fu, Xue-Lei; Wu, Hua; Shen, Wang-Qin; Chen, Hong-Lin
Abstract: Background: This study aims to discuss the expression of matrix metalloproteinase in wound healing of diabetic foot ulcers and further summarize the strategies of targeted matrix metalloproteinase and its inhibitors in the treatment of diabetic foot ulcers. Methods: Following PRISMA-SCR guidelines, databases (PubMed, Home-PMC-NCBI, CINAHL, Web of Science) were systematically searched from inception to 19 June 2022. Newcastle-Ottawa Scale (NOS) was used to evaluate the bias risk of the included studies. Results: Eight studies are finally eligible for our systematic review. The combined data analysis of 8 studies showed that there were no significant difference in age(p = 0.110), duration of diabetes(p = 0.197), glycosylated hemoglobin content(p = 0.489), size(p = 0.133) and depth(p＞0.05) of initial ulcer between the ulcer wound healing group and the non-healing group. MMP-1, 2, 8, 9, and TIMP-1, 2 affected the healing of DFUs. In the DFUs healing group, the concentrations of MMP (MMP-1, 2, 8, 9) decreased, and the concentration of TIMP-1 increased. Conclusion: Our study showed that high levels of MMP-1, 2, 9 delayed the healing of diabetic foot ulcers, and high expression of MMP-8 in tissues improved wound healing. This study also summarized the effective intervention strategies for the treatment of diabetic foot ulcers. Highlights: MMP-1, 2, 8, 9, and TIMP-1, 2 affected the healing of DFUs. In the DFUs healing group, the concentrations of MMP (MMP-1, 2, 8, 9) decreased, and the concentration of TIMP-1 increased. High levels of MMP-1, 2, 9 delayed the healing of diabetic foot ulcers, and high expression of MMP-8 in tissues improved wound healing.